2023
DOI: 10.1177/0271678x221149509
|View full text |Cite
|
Sign up to set email alerts
|

The central role of peripheral inflammation in ischemic stroke

Abstract: Stroke pathology and its treatments conventionally focus on the brain. Probing inflammation, a critical secondary cell death mechanism in stroke, has been largely relegated to the brain. To this end, peripheral inflammation has emerged as an equally potent contributor to the onset and progression of stroke secondary cell death. Here, we review novel concepts on peripheral organs displaying robust inflammatory response to stroke. These inflammation-plagued organs include the spleen, cervical lymph nodes, thymus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 158 publications
0
7
0
Order By: Relevance
“…Firstly, the present study focused on the early molecular changes caused by FD at the onset of cerebral infarction. Considering that post‐stroke neuroinflammation is a highly dynamic and complex adaptive process, 44 long‐term FD intervention may be necessary for further behavioral observation and the exploration of molecular mechanisms at the later stage of disease in the future study. Secondly, both astrocytes and microglia mediate inflammatory responses through related molecules in response to the stress of ischemic brain injury 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the present study focused on the early molecular changes caused by FD at the onset of cerebral infarction. Considering that post‐stroke neuroinflammation is a highly dynamic and complex adaptive process, 44 long‐term FD intervention may be necessary for further behavioral observation and the exploration of molecular mechanisms at the later stage of disease in the future study. Secondly, both astrocytes and microglia mediate inflammatory responses through related molecules in response to the stress of ischemic brain injury 45 .…”
Section: Discussionmentioning
confidence: 99%
“…While we have mainly focused on the role of SCs centrally, a multitude of studies have shown the vital role of peripheral organs in neuroinflammation 93 . As discussed, the BBB is impaired in stroke and MS, facilitating the entry of peripheral inflammatory cells into the typically immunoprivileged CNS.…”
Section: Peripheral Contributionsmentioning
confidence: 99%
“…Ischemic strokes are one of the most prevalent cerebrovascular conditions, significantly contributing to global mortality and disability. 1 , 2 Ischemic strokes encompass a cascade of pathological events, encompassing excessive calcium accumulation, 3 excitotoxicity, 4 increased oxidative stress, 5 , 6 mitochondrial dysfunction, 7 inflammation, 8 , 9 , 10 and cell death. 11 Acute ischemic stroke is a severe medical condition characterized by the interruption of blood flow to the brain due to arterial obstruction.…”
Section: Introductionmentioning
confidence: 99%